Carcinoma cervix with cerebellar metastases presenting with pulmonary aspiration: a rare presentation and a rare metastatic site in a common cancer. Issue 7 (27th July 2019) - Chakrabarti, Deep; Resu, Abigail Veravolu; Pandey, Amit; Gupta, Rajeev
Abstract : A 52-year-old woman with cervical cancer stage IIB presented with altered sensorium and breathlessness to the emergency room 5 months after completing primary chemoradiotherapy, which was diagnosed as aspiration pneumonia. She was found to have cerebellar metastases with additional frontal, occipital, and temporal lobe lesions. She had no evidence of extracranial disease. She received supportive care and palliative whole brain radiotherapy and was asymptomatic at 6 months following radiotherapy. Median reported survival is 8–13 months.